2012
DOI: 10.1007/s00441-012-1461-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of astrocytes in transmissible spongiform encephalopathies: a confocal microscopy study

Abstract: Astroglial proliferation associated with pathological prion protein (PrPsc) deposition is widely described in Transmissible Spongiform Encephalopathies (TSEs). However, little is known of the actual role played by glia in their pathogenesis. The aim of the study has been to determine whether PrPsc is located exclusively in neurons or in both neurons and glial cells present in the central nervous system in a natural Scrapie model. Samples of cerebellum from 25 Scrapie sheep from various flocks were sectioned. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 47 publications
4
17
1
Order By: Relevance
“…Thus, it is most likely that prions induced cytopathic changes in astrocyte lineage cells in dNP20 cultures. However, these observations appear to contradict those of previous studies in which astrocytes were observed to be permissive to prion infection in vivo and in vitro (6,(41)(42)(43)(44); nonetheless, there is no evidence to suggest astrocyte loss or degeneration during prion infection in vivo (45) and in slice cultures (46). A possible explanation for this discrepancy is that dNP20 cultures contained immature astrocytes, and these cells may be susceptible to prioninduced cytotoxicity.…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, it is most likely that prions induced cytopathic changes in astrocyte lineage cells in dNP20 cultures. However, these observations appear to contradict those of previous studies in which astrocytes were observed to be permissive to prion infection in vivo and in vitro (6,(41)(42)(43)(44); nonetheless, there is no evidence to suggest astrocyte loss or degeneration during prion infection in vivo (45) and in slice cultures (46). A possible explanation for this discrepancy is that dNP20 cultures contained immature astrocytes, and these cells may be susceptible to prioninduced cytotoxicity.…”
Section: Discussioncontrasting
confidence: 56%
“…With the purpose of identifying a specific cellular population that seemed to co-localize with PrPsc in several mice, and suggested to be a glial cell due to its morphology and distribution, a confocal microscopy study was carried out following the protocol previously established [28]. …”
Section: Methodsmentioning
confidence: 99%
“…In scrapie affected sheep, astrocytosis is one of the most common described histopathological events related with the disease [65]. Thus, glial activation, which is particularly strong in the Mobl and cSc, might partially explain the CAPN6 expression changes.…”
Section: Discussionmentioning
confidence: 99%